Determinants of Livelihood Diversification Under Environmental Change in Coastal Community of Bangladesh. Issue 1 (December 2020) - Roy, Apurba; Basu, Sudipa
The life and livelihood of coastal farming communities in Bangladesh are highly vulnerable to climate and environmental change. Diversification of farmers' income sources beyond agriculture can be an effective way to cope with the adverse impacts of environmental change. The purpose of this study is to analyse the options and determinants of livelihood diversification (LD) strategies adopted by farmers in the coastal region of Bangladesh. Multiple linear regression technique along with Simpson index, Herfindahl index and priority index have been used for the analysis. Simple random sampling and multistage sampling have been used to select the sample and the study area, respectively. The magnitude of farming household diversification is at medium level. A significant share of annual income comes primarily from fish and rice production, domestic bird rearing and working as agricultural labour. The adoption of diversified activities is strongly influenced by age and education of household head, number of earning family members, social network and government donation. The frequent occurrence of natural disasters, inadequate infrastructure and lack of financial capacity are the critical constraints to LD.